Drama-based education to motivate participation in substance abuse prevention - Cameron Amura; Craft Howard L; Dacons-Brock Karen; Livingston Jonathan N; Stephens-Hernandez Aileen B; Franklin Steven O; Howlett Allyn C (BMC, 2007)
Abstract Background The substance abuse prevention goal of the theatre production "TUNNELS" was to provide community education on substance abuse to an audience in Durham, NC and surrounding communities. The education effort intended to increase awareness and understanding of the risk and protective factors associated with alcohol and other drug use, and to promote pro-active behaviors in substance abuse prevention within the adult community. It was hypothesized that community-based education via drama would change attitudes toward alcohol and substance abuse, and increase participation in family and community activities aimed at substance abuse prevention. Methods A focus group comprised of educators, substance abuse researchers and local substance abuse counselors developed "life stories" of users of alcohol and other drugs and a local playwright incorporated these and other experiences into a series of six vignettes. The production was publicized throughout the Durham area, and 700 adults attending the play signed a consent form and completed the pre-play survey. The participant pool was restricted to those adults who completed both the time-1 and time-2 surveys and resided within Durham and surrounding communities. Paired comparisons of mean responses were analyzed using a paired sample two-tailed t-test. A telephone survey three months after the play assessed attitudes toward substance abuse as a disease, and whether the respondents had increased their participation in prevention activities including discussions of the play with others. Results Viewing the play increased the knowledge base of participants regarding substance abuse as a disease, even though the audience demonstrated an appreciation of risk and protective factors prior to attending the performance. In the pre-play survey, participants indicated a strong opinion that parental involvement in teen life was important, and therefore this was not increased as a result of viewing the play. It was found that the drama increased intent to participate in substance abuse prevention activities at home and in the community. Follow-up surveys performed three months after the performance indicated that participants had discussed the play with others and had increased their participation in substance abuse prevention activities, particularly regarding donations of money. Conclusion Drama incorporates a component of emotional response to the informational content, and the combination of emotion and information works together to promote individual intentions to become more involved in family and community prevention activities. This study demonstrates the efficacy of drama as a mechanism to educate and motivate. Support for this mechanism is warranted at the level of state, local community, school district, and faith-based and community organizations.